Review of speed limit for FR222 access road to Gambang toll - Hazlyza, Zainon (2012)
This thesis presents a review of speed limit on a straight road that relate with road accidents. The main objectives of this study are to investigate excessive speed that can cause road accidents and to recommend appropriate measures for road safety improvement. This study focused on the straight road which is along MEC Highway start from FR222 Access Road to Gambang Toll. This spot speed study was conducted in six days by using radar gun to record the speed based on type of vehicles that passing through on this road. The type of road on this location is Federal Road and area type is Rural categorized as R5. From this study, the result that have obtained able to show the 15 th , 50th 85 th and 95 th speed percentile from the cumulative frequency distribution curves graph. The speed limit that has been set by Department of Work (JKR) on this road is 90 km/hr. The result of this study shows that the highest frequency of vehicle most in speed group 90-99 km/hr. Speed limit that have been obtained from six points on this location of study are 3.62km/br,93.80km/br,98.46km/hr,101.67km/br, 99.74km/br, and 86.02km/hr. The average speed that obtained at six points on this study location is most over the speed limit allowed. The number of drivers that drive over the speed limit is more than the number of drivers that drive under the speed limit. This situation occur maybe due to nonexistence of speed limit signboard and condition of straight road that make drivers tend to drive at excessive speed that can cause road accidents. Suggestions to placement the speed limit signboard, warning to slow down speed signboard and Automated Enforcement System (AES) have been proposed for road safety and accident free in Malaysia.